Public service transformation trough digital-based services during Covid-19 pandemic in Riau Province, Indonesia - Panca Setyo Prihatin; Pahmi Amri; Agung Wicaksono (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
The purpose of this paper is to show how the Riau Provincial Government might transform public services based on digital services in the direction of good governance. This paper then uses a qualitative analysis method with Nvivo 12 Plus as an analytical tool to visualize data from online media sites. The findings of this study indicate that during the Covid-19 pandemic, the transformation of digital service-based public services in Riau Province can be seen from three aspects, namely: First, on the transparency aspect, the Riau Provincial Government has implemented digital services so that they can be more easily accessed. Second, in terms of accountability, every public service provider already has a strong understanding of how to implement digital services. However, the implementation of digital services still faces challenges and requires improving aspects of internet network quality in several locations in remote and underdeveloped areas. Third, in terms of effectiveness and efficiency, the Riau Provincial Government has received various awards for public service innovations and has launched the Mata Bansos application which is intended to help communities affected by Covid-19. Therefore, this research contributes in the form of recommendations to continue to improve public services by utilizing existing digital service applications and further integrating public services that have not been integrated with digital-based services.